The Oxford Book of Military Anecdotes - Edited by Hastings, Max (New York Oxford University Press, 1989)
Max Hastings has assembled a collection of anecdotes which illuminate the condition of the soldier through the ages, in barracks and on the battlefield. The selection embraces both the tragic and the comic, finding room for eccentrics as well as heroes, rankers and generals. Extending from biblical times to conflicts of today, it presents an absorbing record of the glories and tribulations of military life. --Jacket.
Include Index
Keywords: Military art and science -- Military history -- Soldiers